# How do you solve #2|x +(-2)| + (-6) = -4#?

See the entire solution process below:

We must solve the term within the absolute value function for both its negative and positive equivalent because the absolute value function takes any term, whether positive or negative, and converts it to its positive form.

First Solution

Option 2)

By signing up, you agree to our Terms of Service and Privacy Policy

To solve the equation 2|x +(-2)| + (-6) = -4, follow these steps:

- Add 6 to both sides of the equation: 2|x +(-2)| = 2.
- Divide both sides by 2: |x +(-2)| = 1.
- Break the equation into two cases: Case 1: x + (-2) = 1 Case 2: x + (-2) = -1
- Solve each case separately: For Case 1: x + (-2) = 1, add 2 to both sides: x = 3. For Case 2: x + (-2) = -1, add 2 to both sides: x = 1.

So, the solutions to the equation are x = 3 and x = 1.

By signing up, you agree to our Terms of Service and Privacy Policy

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.

- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7